Funeral Festivals in America : Rituals for the Living - Thursby, Jacqueline S., 1940- (Book collections on Project MUSE., 2006)
In this volume, the author explores how modern American funerals and their accompanying rituals have evolved into affairs that help the living with the healing process. Thursby suggests that there is irony in the festivities surrounding death.